Wood Wide Web: communication through the mycorrhizal network - Castro-Delgado, Ana Lucía (2020)
Mycorrhizal fungi are classified as ectomycorrhizae (EM) and endomycorrhizae, which include arbuscular mycorrhizas (AM). They colonize over 80% of land plants roots and provides them with nutrients from the soil and a hyphal network named wood wide web. This review describes the interactions in which mycorrhizal networks are involved. From a practical point of view, EM can be more beneficial than AM for plant development and the relationship between fungi and plants is conditioned by external factors. The investigation also showed that mycelium can transfer a wide variety of compounds and signals among plants that can modify their behaviour to protect the network as a whole. Carbon transfer is an important tool to achieve that and can promote forests regeneration. These findings emphasize the complexity of forests relations, and the importance of study their dynamics to guarantee its conservation.